Collaborative Governance in the Implementation of the Free Nutritious Meal Program: A Study of Cross-Sectoral Coordination at the Regional Level - I Ketut Yoko Putra Kartono; Luh Putu Mahyuni (Bulletin of Community Engagement, 2026)
This study aims to analyze the cross-sector collaborative governance process in the implementation of the Free Nutritious Meal Program (MBG) in Karangasem Regency. The study focuses on four main aspects of the Ansell and Gash model: starting conditions, institutional design, facilitative leadership, and collaborative process. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. The research informants consist of stakeholders from local government, program implementers, and parties involved in the provision and distribution of local food. The findings show that the implementation of the MBG Program in Karangasem Regency is built upon a shared need to address child nutrition problems, poverty, and limited access to nutritious food. However, cross-sector collaboration still faces challenges such as resource imbalances, differences in capacity among actors, and the need to strengthen institutional coordination. Facilitative leadership plays an important role in building trust and shared understanding through dialogue, coordination meetings, and role adjustment among stakeholders. In addition, program sustainability is influenced by supporting factors such as shared commitment, institutional support, and the involvement of local actors, while inhibiting factors include geographical conditions, limited data, and logistical distribution challenges. These findings emphasize that the success of the MBG Program in Karangasem Regency is strongly determined by the quality of collaborative governance that is inclusive, adaptive, and oriented toward program sustainability.